2017
DOI: 10.1093/jpepsy/jsx134
|View full text |Cite
|
Sign up to set email alerts
|

Problems With Self-Regulation, Family Conflict, and Glycemic Control in Adolescents Experiencing Challenges With Managing Type 1 Diabetes

Abstract: These findings suggest that among teens experiencing challenges with managing type 1 diabetes, interventions that decrease family conflict may be critical to promoting optimal glycemic control in those teens with greater problems with self-regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 55 publications
6
18
0
Order By: Relevance
“…In this study, preteens (aged 10-12 years) with T1D reported a better parent-child relationship quality than did teenagers (aged 13-18 years) with T1D. This finding was similar to that found in a U.S. study, which showed that tensions in parent-child relationships peaked among adolescents (aged 13-17 years) (Vaid et al, 2018). As reported previously, adolescents prefer to be independent from their parents, especially when they transition from childhood to adolescence (Fung et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…In this study, preteens (aged 10-12 years) with T1D reported a better parent-child relationship quality than did teenagers (aged 13-18 years) with T1D. This finding was similar to that found in a U.S. study, which showed that tensions in parent-child relationships peaked among adolescents (aged 13-17 years) (Vaid et al, 2018). As reported previously, adolescents prefer to be independent from their parents, especially when they transition from childhood to adolescence (Fung et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…The relative frequency of these themes aligns with the established understanding that adolescents with T1D are moving from dependence to autonomy in their diabetes self‐management during this time period 4,17,32 . We did not observe indication of a positive or negative association between frequency of intention to elicit parent support or frequency of intended joint goals and youth glycemic control in our sample, but it is possible this lack of association is the result of a mixing of effects, and that both goal categories represent a mix of self‐management promoting and challenging parent‐child dynamics (e.g., “adaptive” vs “maladaptive” communication, discrepancies in decision‐making autonomy) that have been shown, respectively, to be favorably and unfavorably associated with youth HbA1c 10,32‐34 …”
Section: Discussionsupporting
confidence: 77%
“…16,18 The most common theme we observed across goal intentions of that have been shown, respectively, to be favorably and unfavorably associated with youth HbA1c. 10,[32][33][34] However, we did observe an unfavorable association between frequency of intention to elicit diabetes-specific, instrumental support (vs. emotional support) from friends or siblings and worsening glycemic control. 32,35 Existing literature on the effect of peer support on T1D self-management is mixed, and mechanisms by which the various types of peer support positively or negatively affect glycemic control have been hypothesized but not clearly elucidated or quantified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have provided some insights regarding the negative effects of family dysfunction on behavioural and health‐related outcomes in youth with T1D. For example, family conflict and less parental monitoring negatively influence self‐management and glycaemic control (Hilliard et al, ; Vaid, Lansing, & Stanger, ). In this study, we tried to identify the roles of positive family relationships.…”
Section: Introductionmentioning
confidence: 99%